Factors related to the Quality of Work Life of nursing at the Hospital - Tham, Le Thi; An, Pham Le (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Burnout is a fairly common syndrome among healthcare workers. As the quality of life improves, the requirements for service quality in most sectors are increasing, which leads to invisible pressures that make many workers, especially medical staff, including nurses, prone to burnout syndrome. So is there a correlation between Burnout and the Quality of Work Life (QoWL) of nursing? Method: A cross - sectional descriptive study was conducted on 123 nurses working in departments of Le Van Thinh Hospital, District 4 Hospital, and Tan Phu District Hospital in Ho Chi Minh City. The sample was selected using a convenient sampling method. Results: The study showed that the burnout rate of nurses at District 4 Hospital, Tan Phu Hospital, and Le Van Thinh Hospital was at a low level of 7.3%. Among them, 10.5% of nurses suffered from Emotional Exhaustion (EE); 39.1% of nurses had a Depersonalization (DP); and 13.0% of nurses experienced a decrease in Personal Accomplishment (PA). There is a correlation between quality of work life and burnout in nurses. Conclusion: The rate of burnout in nurses at District 4 Nursing Hospital, Tan Phu Hospital, and Le Van Thinh Hospital is 7.3%, which is relatively low.